What is normal anyway? Exploring the Effect of Social Norms on Grief Expectations, Expressions, and Social Support - Logan, Enna Louise (Curtin University, 2018)
Social support is a significant predictor of psychosocial outcomes following bereavement. Focused on advancing the community’s capacity to support, this thesis presents a mixed methods investigation of the nature and scope of grief-related norms and their influence on experiences of grief and being supported. This research offers a valuable contribution to the literature through advancing the research field, informing clinical practice with bereaved people, and directing best practice grief education for the general public.